Diagnosing Inherited Platelet Disorders: Modalities and Consequences - Zaninetti, Carlo; Wolff, Martina; Greinacher, Andreas (Hämostaseologie, 2021)
Inherited platelet disorders (IPDs) are a group of rare conditions featured by reduced circulating platelets and/or impaired platelet function causing variable bleeding tendency. Additional hematological or non hematological features, which can be congenital or acquired, distinctively mark the clinical picture of a subgroup of patients. Recognizing an IPD is challenging, and diagnostic delay or mistakes are frequent. Despite the increasing availability of next-generation sequencing, a careful phenotyping of suspected patients—concerning the general clinical features, platelet morphology, and function—is still demanded. The cornerstones of IPD diagnosis are clinical evaluation, laboratory characterization, and genetic testing. Achieving a diagnosis of IPD is desirable for several reasons, including the possibility of tailored therapeutic strategies and individual follow-up programs. However, detailed investigations can also open complex scenarios raising ethical issues in case of IPDs predisposing to hematological malignancies. This review offers an overview of IPD diagnostic workup, from the interview with the proband to the molecular confirmation of the suspected disorder. The main implications of an IPD diagnosis are also discussed.
Keywords: inherited platelet disorders; hereditary thrombocytopenias; bleeding tendency; blood smear; genetic testing